(untitled) (Journal of Partial Differential Equations, 1996)
In this paper, we discuss the regularity of the weak solutions and the existence of the classical solutions for Monge-Ampère equations on the bounded convex domains possessing uniform parabolic support. This paper improves the conclusion of [1].